Resolving Murabahah Default: Legal Substance, Structure, and Culture in Community-Based Islamic Financial Institutions - Evi Rizkia; Abdul Haris Na'im (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: Murābaḥah default in community based Islamic finance institutions is often managed through non litigation pathways, yet its effectiveness boundaries are rarely assessed through a socio legal lens. This study maps patterns of murābaḥah default and the dispute resolution chain at KSPPS Nusa Ummat Sejahtera, Dawe Kudus Branch, then tests legal effectiveness using indicators of legal substance, legal structure, and legal culture. The research adopts a qualitative socio legal case study design, drawing on primary data from interviews with managers and members, and secondary data from internal documents, warning letters, restructuring addenda, and relevant normative references. Findings identify installment payment delay as the dominant default pattern, alongside recurring default after restructuring. The resolution chain proceeds in stages through written warnings, personal approaches, deliberation, internal mediation, restructuring in the form of rescheduling and reconditioning, and collateral based options that seldom escalate to formal forums. The substance test reveals vulnerabilities in members’ contract literacy and tensions in practice concerning wakālah (agency) and asset ownership. The structure test indicates that internal capacity is sufficiently functional for ṣulḥ (amicable settlement), yet remains constrained at the collateral stage and by limited access to external dispute resolution institutions. The culture test shows that kinship-oriented norms accelerate short term settlement but also create tolerance approaching moral hazard and prolong repeated restructuring. Abstrak: Wanprestasi murābaḥah pada lembaga keuangan syariah berbasis komunitas sering diselesaikan melalui jalur non-litigasi, namun batas efektivitasnya belum banyak diukur secara sosio legal. Kajian ini memetakan pola wanprestasi dan rantai penyelesaian sengketa murābaḥah pada KSPPS Nusa Ummat Sejahtera Cabang Dawe Kudus, lalu menguji efektivitas hukum (legal effectiveness) melalui indikator substansi hukum, struktur hukum, dan budaya hukum. Desain penelitian memakai studi kasus kualitatif sosio legal dengan data primer berupa wawancara pengurus dan anggota, serta data sekunder berupa dokumen internal, surat peringatan, addendum restrukturisasi, dan rujukan normatif yang relevan. Temuan menunjukkan keterlambatan angsuran sebagai pola dominan, disertai kecenderungan wanprestasi berulang setelah restrukturisasi. Rantai penyelesaian berjalan bertahap melalui surat peringatan, pendekatan personal, musyawarah, mediasi internal, restrukturisasi berupa rescheduling dan reconditioning, serta opsi penanganan jaminan yang jarang berujung ke jalur formal. Uji substansi mengungkap kerentanan pada pemahaman akad dan ketegangan praktik terkait wakālah dan kepemilikan barang. Uji struktur menegaskan kemampuan internal koperasi cukup fungsional untuk ṣulḥ, namun terbatas pada fase jaminan dan akses lembaga eksternal. Uji budaya hukum memperlihatkan nilai kekeluargaan mempercepat penyelesaian jangka pendek, tetapi membuka ruang toleransi yang mendekati moral-hazard dan memperpanjang restrukturisasi berulang.